Analisis Kerusakan untuk Tindakan Perawatan pada Mekanika Elevator Otis Kapasitas 2 Ton di RSUP Dr M.Djamil Padang - Widi, Widi; Mukhnizar, Mukhnizar; Selviyanty, Veny; Abu, Risal; Afdal, Afdal (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
An elevator is a vertical transportation device used to transport people or goods. Elevators are box-shaped and are generally used in high-rise buildings, usually more than three or four floors. Elevator specifications are determined by its capacity, speed, and carrying capacity. Elevator selection is based on the use of elevators in buildings with traffic, commuting time, peak time and waiting time in terms of capacity (handling capacity), elevator speed. Adequate quantity of vertical transportation is an important factor, because it will affect the quality of service in a building, so maintenance management is needed that can manage elevator performance. The first step in analyzing component repairs is to use direct observation methods, namely primary and secondary data collection, data processing is carried out to extend the service life of Otis elevators, covering the working principles of Otis elevators, knowing the causes of Otis elevator damage, determining the Otis elevator maintenance schedule and knowing how to properly maintain Otis elevators and how to minimize damage that occurs